Covering the 2024 General Election: Journalists' Perceptions of the 2024 General Election Process: Meliput Pemilihan Umum 2024: Persepsi Jurnalis tentang Proses Pemilihan Umum 2024 - Nur, Muhammad Jamiluddin; Muhlis, Muhlis; Teluma, Aurelius Rofinus Lolong; Nurmita, Nurmita; Idaman, Lale Sekar Pratiwi (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2025)
Journalists often observe Indonesia’s elections at close range in real time: gathering data, verifying facts, writing, and publishing accounts of the process. Yet research on journalists’ perceptions of elections remains limited and is usually framed through institutional or media-company perspectives. This study explores how journalists perceived the 2024 general election. Using a phenomenological design, it captured meanings drawn from reporters’ lived experiences of covering the election. Data were generated through in-depth interviews and thematic interpretation of their narratives. Informants were selected purposively: six political reporters in Mataram City from six different media outlets. Findings show a tendency toward negative perceptions of key stages, including presidential–vice presidential nominations, voter-list verification, the cooling-off period, and vote recapitulation. Journalists described the process as still centralized, viewed candidate selection as an economic contest rather than an ideas-driven one, and characterized the cooling-off period as chaotic. The study’s novelty lies in centering local journalists’ individual experiences across nearly all election stages, contrasting with prior work that emphasizes news content, normative journalistic roles, or media–elite relations.